Determining Leading Economic Sectors, by Large Distribution or Extreme Growth? The Case of Tulungagung Regency, Province of East Java - Alfian Rosadi (The Journal of Indonesia Sustainable Development Planning, 2020)
Leading economic sector on Tulungagung Regency determined by sector contribution on GRDP. These sectors expected can be a booster to economic growth. But Economic Growth in Tulungagung Regency was still slower than East Java Province. This Study aims to determined Leading economic sector not only by its contribution. SLQ and DLQ analysis, average contribution, growth rate and shift share analysis have been done to observe contribution, competiveness and progresive growth of economic sector. Based on the assesment by scoring of the criteria, leading economic sector was determined and found that education service sector lead the rank followed by information and communication sector.